2019
DOI: 10.12688/gatesopenres.13029.1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying population segments for effective intervention design and targeting using unsupervised machine learning: an end-to-end guide

Abstract: One-size-fits-all interventions that aim to change behavior are a missed opportunity to improve human health and well-being, as they do not target the different reasons that drive people’s choices and behaviors. Psycho-behavioral segmentation is an approach to uncover such differences and enable the design of targeted interventions, but is rarely implemented at scale in global development. In part, this may be due to the many choices program designers and data scientists face, and the lack of available guidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Improving our understanding of the characteristics of different groups in the population, their risk of being HIV infected and their uptake of HIV testing is essential to design more targeted and tailored prevention and care programs. Clustering analysis, which is an unsupervised machine learning technique, allows us to identify similarity patterns and find hidden sub-groups of people with potentially different risk levels and drivers of having or acquiring HIV[2]. In a previous study, we investigated differences between SSA countries and identified sociobehavioural profiles that coincided with a high HIV prevalence and incidence at the country level[3].…”
Section: Introductionmentioning
confidence: 99%
“…Improving our understanding of the characteristics of different groups in the population, their risk of being HIV infected and their uptake of HIV testing is essential to design more targeted and tailored prevention and care programs. Clustering analysis, which is an unsupervised machine learning technique, allows us to identify similarity patterns and find hidden sub-groups of people with potentially different risk levels and drivers of having or acquiring HIV[2]. In a previous study, we investigated differences between SSA countries and identified sociobehavioural profiles that coincided with a high HIV prevalence and incidence at the country level[3].…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of what motivates private sector health providers, the dimensions of their motivation, and how motivation may be associated with current performance and sustained engagement, can be used as a helpful input to the design of interventions that select for or encourage the development of motivation dimensions that are associated with improved care and reporting (32). For example, interventions can use these tools to identify and recruit health providers with speci c motivational attributes to be part of programs that require greater a nity to non-nancial over nancial motivations (33,34) or frame program or network objectives in a way that appeals to providers with speci c motivational attributes (35). Alternatively, programs can take the perspective that motivation is mutable and develop interventions that are meant to enhance motivational dimensions that are associated with desired behaviors (36).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical comparisons for these features and their relation to distance traveled for treatment was performed using the Mann-Whitney U test. After standardizing data, an unsupervised learning algorithm called K means clustering using SPSS version 23 (IBM Corp., Armonk, NY) was performed to identify distinct clusters of patients with respect to median income, racial makeup, educational level and rural residency ( 18 ). Distance traveled from each cluster was reported in miles.…”
Section: Methodsmentioning
confidence: 99%